Distributed Rendering Based on Fine-Grained and Coarse-Grained Strategy to Speed up Time and Increase Efficiency of Rendering Process - Mansuan, Melki Sadekh; Soewito, Benfano (Bina Nusantara University, 2019)
The purpose of this research was to solve several problems in the rendering process such as slow rendering time and complex calculations, which caused inefficient rendering. This research analyzed the efficiency in the rendering process. This research was an experimental study by implementing a distributed rendering system with fine-grained and coarse-grained parallel decomposition in computer laboratory. The primary data used was the rendering time obtained from the rendering process of three scenes animation. Descriptive analysis method was used to compare performance using speedup and efficiency of parallel performance metrics. The results show that the distributed rendering method succeeds in increasing the rendering speed with speedup value of 9,43. Moreover, the efficiency of processor use is 94% when it is applied to solve the problem of slow rendering time in the rendering process.